Reconstruction of Constitutional Court Decision on Presidential and Vice Presidential Age Limit from Siyasah Qadhaiyyah Perspective - Saputra, Muhammad Febri Eka; Miswardi, Miswardi; Ihsan, Nurkhairat; Fransiska, Nadya; Safitri, Rahmi Surya (Yayasan Lembaga Studi Makwa, 2025)
The Constitutional Court Decision No. 90/PUU-XXI/2023, which allows individuals under the age of 40 to run for vice president if they have held a regional leadership position, has generated widespread public controversy. This study critically evaluates the ruling through the lens of siyasah qadhaiyyah, an Islamic legal-political framework that prioritizes justice ('adl), transparency (shafafiyyah), and public welfare (maslahah). Utilizing a qualitative research design with a case study approach, data were gathered through semi-structured interviews with constitutional law experts, Islamic jurists, and civil society representatives, supported by document analysis and media reviews. The findings indicate that the ruling is perceived by most respondents as politically biased, lacking alignment with the principles of substantive justice, and potentially discriminatory against non-political actors. Concerns also emerged regarding its implications for increased political polarization and diminished public confidence in judicial impartiality.This research contributes to the global discourse on constitutional jurisprudence and Islamic legal theory by integrating siyasah qadhaiyyah as a normative evaluative tool for judicial decisions in Muslim-majority democracies. It highlights the importance of embedding ethical and inclusive principles in legal reform to safeguard democratic integrity. The study concludes by recommending a realignment of Indonesia’s constitutional policies with the values of siyasah qadhaiyyah to ensure fair political participation and strengthen judicial legitimacy within broader democratic governance frameworks.